Effect of Exports and Development Expenditures on Economic Growth Indonesia - Jumiana Jumiana (ProBisnis : Jurnal Manajemen, 2020)
Economic growth is a significant increase in national income in a certain calculation period. This thesis is entitled "The Influence of Exports and Development Expenditures on Indonesia's Economic Growth for the 2003-2012 Period." This study aims to analyze the effect of exports and development expenditures on Indonesia's economic growth, as well as which variables have the dominant influence on Indonesia's economic growth. The data used in this study are 10-year time series data between 2003-2012 which is secondary. Data were obtained from various sources, including the Central Statistics Agency (BPS), and scientific journals and other literatures related to this research topic. The analytical method used in this study is multiple regression analysis which is used to determine the magnitude of the effect of changes in one variable on other variables with the help of SPSS 17. From the regression results above, the value of R squared (R2) is 0.957, this means 95.7% variation changes in economic growth variables can be explained simultaneously by variations in export variables and development expenditures, the remaining 4.3% is determined by other variables or factors outside the model. For exports, the results of the study show that the significance value is smaller than the significant level (0.000 < 0.05) so that Ho is rejected, Ha is accepted, thus exports have a positive and significant effect on economic growth. While for development expenditure, the significant value is greater than the significance level (0.251 > 0. 05) so that Ho is accepted, Ha is rejected, thus the results of the study show that the coefficient of development expenditure is not significant to Indonesia's economic growth. The Indonesian government must pay attention to the role of exports which in fact significantly have a positive influence on national income. Indonesia's exports are still dominated by primary products or raw materials and the low support for infrastructure and superstructure is an obstacle in increasing Indonesia's export productivity. Therefore, good coordination between economic actors and monetary policy makers is needed so that the budget policies taken later do not disturb monetary stability and vice versa.